ECMO therapy in COVID‐19: An experience from Zurich. Issue 5 (30th October 2020) - Sromicki, Juri; Schmiady, Martin; Maisano, Francesco; Mestres, Carlos A.
Abstract: Background: The current coronavirus disease 2019 (COVID‐19) pandemic has a huge impact on society and the economy and represents one of the biggest challenges for healthcare systems all over the world. Reports from healthcare institutions in different countries show a variety of crisis exit strategies. Methods: The following is a review and update of the situation and crisis management in Zürich and Switzerland with a special focus on the impact on the cardiac surgery program and extracorporeal membrane oxygenation (ECMO)‐therapy in COVID‐19. Results: Regional and national measures had avoided the collapse of the health system in Switzerland. There was a reduction of over 50% of the surgical and transcatheter caseload during the first wave of the pandemic. Twenty‐three ECMO devices, 150 oxygenators, and more than 300 different cannulas were at our disposal. Between March and May 2020, nine COVID‐19 patients were treated by us with ECMO‐therapy. Three patients were transported by us from distant institutions. Median age at ECMO implantation was 59 years. Two patients died on support. Conclusions: Measures to prevent a collapse of the healthcare system were effective. Our local ECMO‐Program on the ongoing COVID‐19 pandemic has proven to be a useful tool to control mortality and organ failure in critically ill patients.